(3WQjb QFjS hWQb aQYjI (B:s (3OQGSGJ aj GdEUdGM hGdEfJbGd eG HYO GdTjhYj (B/s - (3chQfGj, LGfhSs; (3GdJd, fGOQ GOQjS s ((3YeGf(B: s (3OGQ GdcJGH GdMOjK ddfTQ hGdJhRjY(B, s, 1998)
(3GTJQGcjI GdShb GdeYGO aMUgG, GdUdI Hjf CTcGd GdedcjI hBdjGJ GdJfSjb, WQjb GdGJMGO GdShajGJj Edi GdGbJUGO GdMQ(B:(3JYdjbGJ eQGbH NGQLj, eHGOF GdNUNUI aj GQhHG GdTQbjI, GdGfJbGd eG HYO GdGTJQGcj hGdOhdI, JCedGJ aj VhA GdTcdGJ GdeGdjI GdgfZGQjI, GdJWhQ GdJOQjLj ddGfVHGW GdeGdj aj Xd GdfSb eG HYO GdGTJQGcj, GdQchO GdJMhjdj, XGgQI YGeI eaMhUI ef NdGd eKGd JWhQ gfZGQjG, GdGfJbGd eG HYO GdGTJQGcj(B: (3eQGLYI YGeIs
(3GdeQGLY U(B.235s
Keywords: (3GdGTJQGcjIs; (3GdGbJUGO(B- (3JGQjNs